Carrying out thermodynamic calculations and definition of the main reactions of decomposition of vapours of ethyl alcohol; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Sechin A. I. Aleksandr Ivanovich (2015, 2015)
Title screen